ADAPTER: Analysing and developing adaptability and performance in teams to enhance resilience. (September 2015) - van der Beek, Dolf; Schraagen, Jan Maarten
Abstract: In the current study, the concept of team resilience was operationalized by developing a first version of a questionnaire (ADAPTER) driven by the four essential abilities of resilience (Hollnagel E, 2011, Resilience engineering in practice: a guidebook, p. 275–96) and expanded with more relation-oriented abilities of leadership and cooperation. The development and administration of ADAPTER took place within two companies. Factor analyses using data of 91 participants largely supported the hypothesized 6-dimension taxonomy. Support was found for Team responding behavior, Shared Leadership and Cooperation with other teams/departments. Anticipation showed considerable overlap with the monitoring scale, possibly due to the fact that monitoring items dealt with prospective situations. Using ADAPTER questionnaire results as a starting point for further in-depth discussion among the different teams in the pilot companies proved very useful. Suggestions for future research include contextualizing the questionnaire by embedding it in actual cases or having it filled in after specific incidents. Also, support of organization should be included as a separate dimension in ADAPTER. Highlights: Development of a team resilience questionnaire (ADAPTER). Driven by Hollnagel׳s resilience abilities plus shared leadership and cooperation. Pilot testing of ADAPTER took place within two companies. Factor analyses ( N =91) largely supported the hypothesized 6-dimension taxonomy. Results provide a useful starting point for further in-depth discussions.